RHYMES ARE FORMED IN THE POETRY OF THE UMAYYAD POETS AL-MUQALLIN )THE BOOK OF UMAYYAD POETS AS A MODEL ( - Maryam Mohsen Saleh; Luma Saadoun Jassim Al-Qaisi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Praise be to God, Lord of the worlds, and the best prayer for His faithful Prophet, who was sent as a mercy to the worlds, Muhammad, his family and all his companions, and those who followed their path until the Day of Judgment, and after: The poetry of the submerged fried poets is a wellspring of poetic creativity, but because of the lack of their poems, and the disappearance of some of them, these poets are made dumb in studies. The reluctance of most students to engage in performances made me defy the odds to prove my worth for myself and my teachers in this specialty. Perhaps my passion for performances was one of the most powerful motives I invested in revealing the musical formation that characterized this category of poets in the Umayyad era .